Are Students of Secondary Schools of Seven Districts Different on Their Self-Estimates of Multiple Intelligences? A Case Study of Southern Districts of Khyber Pakhtunkhwa - Shahzada, Gulap; Khan, Habib Nawaz; Muhammad Khan, Ayaz; Ullah, Hakim (Frontiers in Education, 2021)
Self-assessment of intelligence is a personal belief of ability, which is counted for an important portion of success in life. On 905 students of secondary school of seven districts of Khyber Pakhtunkhwa, a survey study was conducted in order to find out students’ self-estimates and the differences of self-estimates on multiple intelligences. Data was collected from the subjects through a valid and reliable inventory. For selection of the sample a stratified random and proportion allocation technique were used; Tests of Between-Subject effects, analysis of variance and Post hoc were applied as inferential statistical test. Result of the study revealed that students of Lakki Marwat estimated their logical/mathematical, intrapersonal, verbal/linguistic, visual/spatial intelligence higher than the other districts students. Students of Bannu rated their musical intelligences higher than the students of other districts. Students of Hango estimated their bodily/kinesthetic intelligence higher than the students of other districts. Students of Kohat estimated their existential intelligence higher than the students of other districts. Researcher suggested that school, should give such an environment of learning to the students where all the intelligences can be focused and promoted.